2012
DOI: 10.1371/journal.pone.0049862
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 Mediates Exacerbated Ca2+ Entry in Dystrophic Skeletal Muscle

Abstract: There is substantial evidence indicating that disruption of Ca2+ homeostasis and activation of cytosolic proteases play a key role in the pathogenesis and progression of Duchenne Muscular Dystrophy (DMD). However, the exact nature of the Ca2+ deregulation and the Ca2+ signaling pathways that are altered in dystrophic muscles have not yet been resolved. Here we examined the contribution of the store-operated Ca2+ entry (SOCE) for the pathogenesis of DMD. RT-PCR and Western blot found that the expression level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 69 publications
8
52
0
Order By: Relevance
“…It was also suggested that m-calpain can actually be activated by active ÎŒ-calpain [4]. A corroborative evidence for direct relation between the activities of calpains and of ORAI1 channels had been demonstrated in murine model of Duchenne muscular dystrophy, where inhibition of ORAI1 by its specific inhibitor BTP-2 greatly reduced the cytosolic ÎŒ-calpain activity in the muscle fibres [39], and in skin keratinocytes, for which Ca 2+ - and calpain-dependent pathway is necessary for proliferation, differentiation and migration [40]. …”
Section: Discussionmentioning
confidence: 97%
“…It was also suggested that m-calpain can actually be activated by active ÎŒ-calpain [4]. A corroborative evidence for direct relation between the activities of calpains and of ORAI1 channels had been demonstrated in murine model of Duchenne muscular dystrophy, where inhibition of ORAI1 by its specific inhibitor BTP-2 greatly reduced the cytosolic ÎŒ-calpain activity in the muscle fibres [39], and in skin keratinocytes, for which Ca 2+ - and calpain-dependent pathway is necessary for proliferation, differentiation and migration [40]. …”
Section: Discussionmentioning
confidence: 97%
“…Cytosolic calcium concentration is tightly regulated in muscle fibers and the plasma membrane plays an important role in this regulation through integral membrane proteins controlling both calcium entry and efflux. Defective calcium influx or efflux across the plasma membrane has already been shown to be involved in elevated calcium concentration occurring in Duchenne muscular dystrophy resulting from dystrophin deficiency (Deval et al, 2002; Vandebrouck et al, 2002; Zhao et al, 2012). Among the integral membrane proteins, voltage-activated, store-operated, and stretch-regulated channels represent the main ways of entry whereas Na + /Ca 2+ -exchanger or Ca 2+ -ATPase pump are involved in calcium extrusion (Vallejo-Illarramendi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was already proposed that a pool of TRPV2 at the sarcolemma could be constitutively active and that Ca 2+ entry may promote the addressing of cytoplasmic TRPV2 in dystrophic cardiomyocytes [43]. Moreover, the constituents of SOCs, Orai and TRPC1 proteins, were shown to support elevated calcium influx after store depletion in dystrophic myotubes and fibres, when deficient in dystrophin [29,31,32]. Interestingly, TRPC1 was also suggested to support a constitutive calcium entry in skeletal muscle fibres when deficient in homer-1 [64], and we showed that the scaffolding protein α1-syntrophin prevents exacerbated TRPC1-dependent cation entry in skeletal myotubes [31].…”
Section: Discussionmentioning
confidence: 99%
“…In dystrophic fibres, TRPC1 have been involved in abnormal Ca 2+ influx [29] and Ward et al [30] have shown that expression level of TRPC1 was increased in aged mdx -DCM heart. TRPC1 was also shown to support elevated store-operated calcium entry in dystrophin deficient myotubes and fibres [29,31] as well as Orai1 in FDB fibres [32]. Studies in heterologous system demonstrated that TRPC1 expression induced a 10-fold increase of SAC ns currents and TRPC1 inhibition through RNA anti-sens reduced these currents [33].…”
Section: Introductionmentioning
confidence: 99%